Beyond Misconduct: A New Perspective on Delinquent Adolescents - Majid, Mariam Abd; Hamdi Usman, Abur; Mohamad, Noraini; Azizan, Nurzatil Ismah; Haridi, Noor Hafizah Mohd; Ismail, Zainab; Rahman, Aisyah Humairak Abdul (Jurnal Ilmiah Peuradeun, 2025)
The generation of present-day adolescents is the future national asset, by which this group has a vital role in the future leadership and governance of the country. However, countless cases and news of teenagers’ involment in social misconduct pose a great concern to various parties. The rise in the cases of adolescents’ involment in delinquency misconduct poses a great concern to society. It shows the need for effort to encircle it. The research gap of this article is due to lack of knowledge about delinquent adolescents among society. Therefore, this article aims to identify a definition of delinquent juvenile. The method used is qualitative, and the main instrument of the study is SLR (Systematic Literature Review). A rigorous criteria for inclusion of studies was developed, comprehensive search strategies were employed to identify eligible published studies. Twelve studies based on 880 articles reviewed met the inclusion criteria. A detailed discussion of these 12 literature reviews is presented through two dimensions, the differences and similarities in the definition of delinquent adolescents. Hence, the findings of this study propose the definition of delinquency indirectly is all misconduct leading to negative things that damage the morals and personality of an individual adolescent and negatively impact the adolescent himself, his family, race, religion, and country. The findings greatly can contribute to the corpus of knowledge on adolescents and delinquents.